Gambaran Faktor – Faktor yang Mempengaruhi Terjadinya Kekambuhan pada Pasien Hipertensi - Neli Izatil Minah; Erna Melastuti; Ahmad Ikhlasul Amal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Blood pressure that is higher than normal is known as hypertension. This is a disease to be wary of because it has no signs and symptoms. Recurrence experienced by a person more than once with characteristics that occur frequently and are usually unpleasant. Several factors that influence compliance with treatment, family history, stress, diet compliance. This research aims to identify factors that play a role in the occurrence of relapse in hypertension patients. This research uses a quantitative approach with a descriptive method, which aims to describe the phenomenon in a certain population. Data were collected through the MMAS-8, PSS, and DASH questionnaires from 140 respondents selected using purposive sampling techniques. Based on the results of research from 140 respondents suffer from hypertension, it can concluded that majority were 57 people (40.7%), 76 people were female (54.3%), 137 people were married (97.9%), 53 people had a high school education level. people (37.9%), the longest duration of suffering from hypertension is 1-5 years as many as 62 people (44.3%), the occupation of respondents who work is 86 (61.4%), genetics and family history are the most many families, 88 people (62.9%), 79 people (56.4%) were moderately compliant with medication, 105 people were moderately stressed (75.0%), and 132 people were compliant with diet (94.3%). The results of this research revealed that a number of factors that contribute to recurrence in hypertensive patients include age, gender, marital status, education level, duration of illness, family history, compliance with treatment, stress levels, and compliance with diet.